(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1859)
Alexander Henry Rhind discusses four barrows that he excavated along the banks of the River Wick on the Sibster estate. He comments on the importance of relying on empirical evidence rather than local folklore or arguments that rely on assumptions about past geographical conditions. Meeting notes for March 9, 1857 are appended. The Secretary John Stuart reported back on the letter that the Society sent to the Lord Clerk-Register about Protocol Books. He agreed to the importance of these records but would not request that these books be sent to the General Register House. However, in his reply the Lord Clerk-Register agreed that he would accept donations of Protocol Books if the Fellows of the Society could convince collectors to send them to the General Register House.